Active Ageing: Concept Review Under the Context of Thailand - Benjapongs, Srundit; Chaowsangrat, Chaowarit; Samart, Phasai (Rajapark Journal, 2024)
Due to the global trend of an aging society, including in Thailand, there are attempts to propose ideas to solve the problem of the Aging society. The idea that is often applied is the concept of Active Ageing. This article aims to study the literature to explain the concept of Active Ageing, a policy framework initiated by the World Health Organization (WHO) to provide a guideline for countries to follow. The goal is to enhance the quality of life for the elderly by offering opportunities for good health, social participation, and financial security. Active Aging can lead to successful aging. Result of the literature review found in the context of Thailand, the concept of Active Ageing adheres to and references the policy framework and principles of the WHO, with a primary focus on health issues. Thailand has initiated the National Elderly Plan and later enacted the National Elderly Law, with the implementation of these policies ongoing for a long time. All policy objectives align with the goals of Active Ageing. Research on Active Aging in Thailand encompasses various aspects and is not limited to a single discipline. The various studies aim to develop comprehensive measures to promote Active Aging among the Thai elderly. All research findings can be used for academic purposes or practical applications to benefit the daily lives of the elderly and serve as policy recommendations.